Bottom Structure Repair and FRP Carbon Installation to Increase The Capacity and Performance Of Jetty (Case Study: Jetty Structure Repair – Pax Ocean, Batam) - Donny Arahman Racasiwi; Rifa'i, Andri Irfan (Journal of Civil Engineering and Planning (JCEP), 2024)
This study focuses on the repair of substructure and the installation of carbon FRP to enhance the capacity and performance of a pier, with a case study at Pax Ocean Batam. A pier, which is infrastructure extending into the sea and often exposed to chloride-containing seawater, is prone to concrete corrosion that can shorten the structure’s lifespan. To ensure the safety and operational continuity of the pier, structural evaluation through field inspections, structural testing, analytical modeling, and repair recommendations is necessary. The study employs a quantitative research method, using primary data obtained from field surveys and secondary data from related documents. Non-Destructive Testing (NDT) using Ultrasonic Pulse Velocity (UPV) was conducted to assess the quality of the concrete and the extent of cracking. The findings indicate that the concrete quality is generally in the good to moderate range, though some areas require repair. Repairs were focused on areas with damage, such as delaminated concrete and cracking. To improve the structural capacity, reinforcement with Carbon Fiber Reinforced Polymer (CFRP) was applied. The repair recommendations include strengthening the damaged slabs, beams, and columns to ensure the safety and optimal performance of the pier.